The peculiarities of questioning of minors: problems and solutions - Dorosinskaia, Anna; Bliznyuk, Irina (Полицейская и следственная деятельность, 2020)
The research subject is the questioning of juvenile participants of criminal proceedings; the research object is the peculiarities of this investigative procedure. The research is of a theoretical nature; the authors analyze and study the particular aspects of the questioning of minors. The research is based on the formal-legal, comparative-legal and the systems methods. The authors study in details such aspects of the issue as juvenile crime statistics for 2008 - 2020 and the factors promoting its growth. Special attention is given to the preparation for the questioning and the very procedure of questioning of a juvenile person. The article contains preliminary and final conclusions. The authors consider the participants to the procedure of questioning of minors whose presense at the procedure is required, and the temporal limits for such an interrogation established by law. The urgency of studying the specificity of the status of a children's counsel is determined by the need for its statutorization, and contains in itself the novelty of the research. The formalization of the modernization of the conditions of the questionning of minors, and the issues of acceptability of its repetitive conduction are of a practical importance for law-enforcement activities. For the purpose of a comparative analysis, the authors consider the procedural peculiarities of the questioning of minors contained in the criminal procedure laws of China and Japan.